Wnt-Responsive Lgr5(+) Globose Basal Cells Function as Multipotent Olfactory Epithelium Progenitor Cells - Chen, Mengfei (Society for Neuroscience, 2014)
Persistent neurogenesis in the olfactory epithelium provides a unique model to study neural stem cell self-renewal and fate determination. In the olfactory neuroepithelium, globose basal cells (GBCs) are considered to be the direct progenitors of olfactory neurons. However, the study of neurogenesis from GBCs has been impeded by the paucity of GBC-specific markers. Here we report that Lgr5, a recently discovered adult stem cell marker, is exclusively expressed in GBCs in neonatal and adult mice. Lgr5(+) cells display characteristics of cycling stem cells, including Ki67 expression and EdU incorporation. Lineage tracing analysis demonstrates that Lgr5(+) GBCs regenerate multiple cell types under normal turnover condition or after olfactory lesion. Furthermore, upregulation or downregulation of Wnt signaling in vivo indicates a key role of Wnt signaling not only in maintaining Lgr5(+) cell proliferation and promoting neuroregeneration, but also in delaying sensory neuron maturation. Together, our observations provided new insights into the dynamics of neurogenesis in the olfactory epithelium.